1981
DOI: 10.1093/nar/9.6.1451
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic tree derived from bacterial, cytosol and organelle 5S rRNA sequences

Abstract: ABSTACTA phylogenetic tree was constructed by computer analysis of 47 completely determined 5S rRNA sequences. The wheat mitochondrial sequence is significantly more related to prokaryotic than to eukaryotic sequences, and its affinity to that of the thermophilic Gram-negative bacterium Thermus aquaticus is comparable to the affinity between Anacystis nidulans and chloroplastic sequences. This strongly supports the idea of an endosymbiotic origin of plant mitochondria.A comparison of the plant cytosol and chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 22 publications
1
33
1
Order By: Relevance
“…These have been shown to be highly homologous to the bacterial 16 S rRNA with strong conservation of their 3'-terminal sequences [18]. In Figs 2A and 3 the 3'-terminal sequences of the depicted rRNA is identical between E. colt rRNA and chloroplast 16 S rRNA [14,15].…”
Section: Resultsmentioning
confidence: 87%
“…These have been shown to be highly homologous to the bacterial 16 S rRNA with strong conservation of their 3'-terminal sequences [18]. In Figs 2A and 3 the 3'-terminal sequences of the depicted rRNA is identical between E. colt rRNA and chloroplast 16 S rRNA [14,15].…”
Section: Resultsmentioning
confidence: 87%
“…rRNA genes are widely used for estimation of evolutionary history and taxonomic assignment of individual organisms (14,26,(50)(51)(52). The choice of rRNA genes as optimal tools for such purposes is based on both observations and assumptions of ribosomal conservation (13,50).…”
mentioning
confidence: 99%
“…Comparison of the primary structures of eukaryotic and prokaryotic 5S RNAs led to a universal four-helix model (4) that is generally accepted to be a minimal secondary structure model. For eukaryotic 5S RNA, the model can be extended to a five-helix model (10)(11)(12)(13).Although they have a common ancestry, prokaryotic and eukaryotic 5S RNAs are structurally distinct. Moreover, 50S ribosomal reconstitution experiments showed that different prokaryotic 5S RNAs are functionally interchangeable whereas eukaryotic 5S RNAs cannot replace the prokaryotic molecule in bacterial ribosomes (14).…”
mentioning
confidence: 99%